EVALUATION OF THE LEVEL OF PATIENT SATISFACTION WITH PHARMACY SERVICES AT Dr. J.P. WANANE, SORONG DISTRICT - Pasulu, Yusran Timang; Budiyanto, Angga Bayu; Astuti, Ratih Arum (LPPM Universitas Jambi, 2023)
At this time, the level of public awareness about the importance of health is increasing. This is especially true in providing more and more health services. And quality of service is also needed to ensure satisfaction with health services, one of which is pharmacy. increases and does not cause disappointment for consumers. This research used a sample of 100 respondents. The research was carried out with a descriptive quantitative design by collecting data through observation data and questionnaires, totaling 10 questions representing 5 aspects. All data obtained and collected in this research were primary data. In this research the variable is focused on the level of satisfaction. Satisfaction is seen from 5 dimensional aspects, namely the empathy dimension, reliability dimension, facility dimension, confidence dimension and responsiveness dimension. The results of the first question related to the reliability dimension aspect were 68.2% and 75.6%. The second question related to the empathy dimension aspect received a score of 68.6% and 75.6%, while the third question related to the responsiveness dimension aspect received a score of 77.4% and 73. % The fourth question related to the dimension of confidence received a score of 64% and 78.2% and the fifth question regarding the aspect of the facility dimension received a score of 77.8% and 67.4%